Home range, space use, and vertical distribution of Nassau grouper (Epinephelus striatus) during non-spawning times in Western Puerto Rico - Tuohy, Evan; Schärer-Umpierre, Michelle; Penrod, Louis; Appeldoorn, Richard (Frontiers in Marine Science, 2023)
Understanding animal space use patterns is critical for ecological research and conservation efforts. An organism’s home range territory serves as the fundamental unit of space use and is the area repeatedly used for routine activities. Nassau grouper, Epinephelus striatus, once of high commercial fishery importance, are now on the IUCN’s Red List designated as Critically Endangered due to overexploitation. Known for the formation of large spawning aggregations, information on their movements and space use dynamics outside of the reproductive period are lacking. In this study, we used acoustic telemetry to quantify the non-spawning horizontal and vertical space use patterns of Nassau grouper at the Bajo de Sico seamount, a seasonally closed marine protected area (MPA) in Puerto Rico. Twenty-nine groupers were tagged with acoustic transmitters, of which, fourteen were tracked continuously over a three-year period. Tagged individuals displayed high site fidelity to home reef locations and individuals occupied home ranges of relatively small size that remained constant between years. There was a high degree of overlap of home range territories and in locations where multiple individuals occupied the same home reef, individuals maintained discrete vertical distributions. Nassau groupers were recorded making multiple forays to the spawning site outside of the reported spawning season, and two individuals underwent home reef site relocation. Results indicate relatively low contribution to ecological connectivity during the non-reproductive period, therefore high relative abundances of this species are needed to fulfill their ecological role at the community level. The results also highlight the importance of Bajo de Sico, an isolated seamount of relatively deeper depth, as critical habitat for primary home reef sites of Nassau grouper. These results provide a basis for adapting the current management strategy at this MPA to provide adequate protection to the non-spawning population of Nassau grouper.